Plan de muestreo para la inspección de lotes de producción en el taller de procesos cárnicos ESPAM-MFL - Cedeño Santana, Ana Mercedes (2013)
This study proposes a sampling plan to improve the production batches in the meat-processing workshop. Various tools were applied to conduct a strengths, opportunities, weaknesses, and threats analysis (SWOT–IMPACT) of the facility; observation checklists were used to examine the workshop’s different areas. A survey was also administered, posing the following question: “Do you believe the workshop needs a designed administrative and production sampling-plan model that allows evaluation of batches in the meat-processing workshop?” The survey—addressed to Agroindustry students from the seventh to the tenth semester—yielded an acceptance rate of 82.4 %. The purpose of this plan is to present the basic criteria for sampling meat products and to serve as a support tool for the technician involved in sampling procedures for evaluating the physical and chemical quality attributes of food, in accordance with the requirements of the NTE INEN 1338:96 standard on each production line, thereby improving all aspects of the product during its manufacture. Finally, the study offers recommendations for establishing a sampling plan—presented as a procedural guide—that specifies how many samples to take from a batch, where to take them, and how to handle them to ensure, as far as possible, their physical, chemical, and microbiological.